Performance analysis of MIMO communication system with NLOS UV channel - Vasilyev, Gleb Sergeevich; Kuzichkin, Oleg R.; Surzhik, Dmitry I. (Photonics Letters of Poland, 2020)
Performance analysis is carried out, of a multiple input, multiple output (MIMO) ultraviolet (UV) communication system with a non-line-of-sight (NLOS) UV channel. The achievable bit error coefficient is calculated using three spatial multiplexing methods for different bitrate values, azimuthal deviation between the directional diagrams of an optical transmitter and an optical receiver, and different noise levels. Full Text: PDF References Z. Xu, B. Sadler, "Ultraviolet communications: potential and state-of-the-art", IEEE Commun. Mag. 4667-73 (2009). CrossRef D. Han, Y. Liu, K. Zhang et al., "Theoretical and experimental research on diversity reception technology in NLOS UV communication system", Opt. Expr. 20(14), 15833 (2012). CrossRef Q. Guo, N. He, Z. He, "Research on the channel performances and transmission in UV-LED scatter communications", Study Opt. Comm. 3, 64 (2013). DirectLink G. Chen, L. Liao, Z. Li et al., "Experimental and simulated evaluation of long distance NLOS UV communication", Communication Systems, Networks and Digital Signal Processing (CSND-SP), 9th Int. Symp. on IEEE, 904-909 (2014). CrossRef M.A. El-Shimy, S. Hranilovic, "Spatial-Diversity Imaging Receivers for Non-Line-of-Sight Solar-Blind UV Communications", J. Lightwave Techn. 33(11), 2246 (2015). CrossRef G. Shaw, M. Nischan, M. Iyengar, S. Kaushik, M. Griffin, NLOS UV communication for distributed sensor systems, Proc. SPIE 412683, 96 (2000). CrossRef I.S. Konstantinov, G.S. Vasyliev, O.R. Kuzichkin, D.I. Surzhik, I.A. Kurilov, S.A. Lazarev, "AUV Link Mobile Ad-Hoc Network Examination", J. Eng. Adv. Techn. 8(5S) July 2019 CrossRef I.S. Konstantinov, G.S. Vasilyev, O.R. Kuzichkin, I.A. Kurilov, S.A. Lazarev, "Modeling and Analysis of the Characteristics of Ultraviolet Channels under Different Conditions of Radiation Propagation for the Organization of Wireless AD-HOC Network", J. Adv. Res. Dynam. Contr. Syst. 07, 1853 (2018) DirectLink I.S. Konstantinov, G.S. Vasyliev, O.R. Kuzichkin, D.I. Surzhik, I.A. Kurilov, S.A. Lazarev, "Development Of Uv Communication Channels Characteristics Modeling Algorithm In A Mobile Ad-Hoc Network", J. Adv. Res. Dynam. Contr. Syst. 11(08), 1920 (2019). CrossRef G. Chen, F. Abou-Galala, Z. Xu, B.M. Sadler, "Experimental evaluation of LED-based solar blind NLOS communication links", Opt. Expr. 16(19), 15059 (2008). CrossRef